Past, Present, and Plans for Transit-Oriented Communities in Worcester, Massachusetts - Thibault, Emily (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Christine Cousineau.; Committee: Shan Jiang, and Shomon Shamsuddin.; Keyword: Urban planning.